Functional Polycarbonates from Carbon Dioxide and Tailored Epoxide Monomers: Degradable Materials and Their Application Potential. (8th January 2018) - Scharfenberg, Markus; Hilf, Jeannette; Frey, Holger
Abstract: Aliphatic polycarbonates synthesized from carbon dioxide (CO2 ) and epoxides are resource‐saving, highly biocompatible and biodegradable polymers. Since the discovery of the copolymerization of epoxides and CO2 in 1969 by Inoue et al., this has become an important and useful technology for the large‐scale utilization of CO2 in chemical synthesis, employing mainly propylene oxide, and cyclohexene oxide (CHO). Only in recent years, functionalized polycarbonates have become an emerging topic with a broad scope of potential applications. This review summarizes synthetic routes and properties of numerous functionalized polycarbonates synthesized from CO2 and functional epoxide monomers. Implications for new materials and possible applications, for instance for pharmaceutical purposes and membranes are reviewed. Besides polycarbonates based on oxirane and CHO derivatives, particular emphasis is placed on the manifold synthetic approaches and postpolymerization modifications of glycidyl ether based polycarbonates. Not only functionalized linear polycarbonates are presented but also a variety of novel polycarbonate architectures, e.g., star and hyperbranched polymers. Abstract : Functionalized aliphatic polycarbonates based on carbon dioxide (CO2 ) and tailored epoxide building blocks are a resource‐saving option for a variety of materials and for applications capitalizing on biodegradability and biocompatibility. Besides linear polycarbonates, di and triblock copolymers with polyether and polyester segments as well as other tailored polymer architectures, e.g., amphiphilic and multiarm star polycarbonates, offer great promise as degradable functional materials.